ANALISISIS KEWENANGAN PEMERINTAHAN DAERAH DALAM MENAMBAH PAD DI KABUPATEN MAYBRAT PROVINSI PAPUA BARAT - Bernard Sagrim; Khasan Effendy; Ngadisah; Sampara Lukman (GoAcademica Research dan Publishing, 2020)
Maybrat Regency is one of the provinces located in West Papua province which was formed based on Law No. 13 of 2009 as a result of the division of Sorong Regency. As a new autonomous region, Maybrat Regency needs to increase local revenue (PAD) for the welfare of its people. Original Regional Income is a picture of the potential for regional finance which is generally based on local taxes and levies. Until now, the regional government of Maybrat district has not played an optimal role in increasing PAD. This study aims to analyze the authority possessed by the Maybrat district government in an effort to increase local revenue. This research uses a qualitative design using the post positivism paradigm, which seeks to reveal a social reality that ontologically can never be fully understood due to the limitations of human nature. The research results reveal that in the context of special autonomy, it gives wider authority to local governments in optimizing all the potential that exists to increase local revenue (PAD), such as in terms of managing the economy, governance, service affairs and cooperation with other parties.